Alcohol-impaired Walking in 16 Countries: A Theory-Based Investigation. (September 2021) - Oviedo-Trespalacios, Oscar; Çelik, Ali Kemal; Marti-Belda, Ana; Włodarczyk, Anna; Demant, Daniel; Nguyen-Phuoc, Duy Q.; Rubie, Elisabeth; Oktay, Erkan; Argandar, Gabriel Dorantes; Rod, J.E.; Natividade, Jean Carlos; Park, Joonha; et al.
Highlights: Alcohol-impaired walking is a frequent behaviour internationally. International groups of pedestrians were identified based on their psychosocial characteristics. Perceived risk predicted intentions of alcohol-impaired walking across 16 countries. Japanese pedestrians' intention of alcohol-impaired walking was not predicted using classical TPB variables. Abstract: Alcohol is a global risk factor for road trauma. Although drink driving has received most of the scholarly attention, there is growing evidence of the risks of alcohol-impaired walking. Alcohol-impaired pedestrians are over-represented in fatal crashes compared to non-impaired pedestrians. Additionally, empirical evidence shows that alcohol intoxication impairs road-crossing judgements. Besides some limited early research, much is unknown about the global prevalence and determinants of alcohol-impaired walking. Understanding alcohol-impaired walking will support health promotion initiatives and injury prevention. The present investigation has three aims: (1) compare the prevalence of alcohol-impaired walking across countries; (2) identify international groups of pedestrians based on psychosocial factors (i.e., Theory of Planned Behaviour (TPB) and perceptions of risk); and (3) investigate how segments of pedestrians form their intention for alcohol-impaired walking using the extended TPB (i.e. subjective norm, attitudes, perceived control, and perceived risk). A cross-sectional design was applied. The target behaviour question was "have you been a pedestrian when your thinking or physical ability (balance/strength) is affected by alcohol?" to ensure comparability across countries. Cluster analysis based on the extended TPB was used to identify groups of countries. Finally, regressions were used to predict pedestrians' intentions per group. A total of 6, 166 respondents (Age M(SD) = 29.4 ( 14.2 ); Males = 39.2%) completed the questionnaire, ranging from 12.6% from Russia to 2.2% from Finland. The proportion of participants who reported never engaging in alcohol-impaired walking in the last three months ranged from 30.1% (Spain) to 83.1% (Turkey). Four groups of countries were identified: group-1 (Czech Republic, Spain, and Australia), group-2 (Russia and Finland), group-3 (Japan), and group-4 (final ten countries including Colombia, China, and Romania). Pedestrian intentions to engage in alcohol- impaired walking are predicted by perceptions of risk and TPB-psychosocial factors in group-1 and group-4. Favourable TPB-beliefs and low perceived risk increased alcohol-impaired walking intentions. Conversely, subjective norms were not significant in group-2 and only perceived risk predicted intention in group-3. The willingness of pedestrians to walk when alcohol-impaired differs significantly across the countries in this study. Perceived risk was the only common predictor among the 16 countries.